Analysis of Risk Determinants with Diarrhea Incidence in Toddlers - Kurniawan Koni; Muhammad Isman Jusuf; Laksmyn Kadir (GLOBAL HEALTH SCIENCE GROUP, 2026)
According to the World Health Organization (WHO), diarrhea is a leading cause of morbidity and mortality among children worldwide, particularly in developing countries. Environmental factors, including access to clean water, adequate sanitation facilities, and community hygiene practices, play a significant role in the incidence of diarrhea. This study aims to analyze the risk determinants associated with diarrhea incidence in toddlers in the coastal area of Lake Limboto, Gorontalo Regency. This quantitative study employed an analytical design with a cross-sectional approach. A total of 84 respondents were selected using simple random sampling. Data were collected on variables including respondent knowledge, socio-cultural factors, environmental sanitation, handwashing practices, formula milk feeding, food preparation patterns, and complementary feeding. Statistical analyses were conducted using the chi-square test to determine the bivariate association between each independent variable and diarrhea incidence in toddlers, followed by multivariate analysis using logistic regression to identify the most significant risk determinants. The analysis revealed significant relationships between diarrhea incidence in toddlers and the following variables: respondent knowledge (ρ = 0.01), socio-cultural factors (ρ = 0.01), environmental sanitation (ρ = 0.02), handwashing with soap (ρ = 0.00), formula milk feeding (ρ = 0.01), food cooking patterns (ρ = 0.01), and provision of complementary foods (ρ = 0.01). All examined variables were significantly associated with the incidence of diarrhea in toddlers in the coastal area of Lake Limboto.